ANALISIS FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Fitriyanti; Siti Rohmah (OBOR: Oikonomia Borneo, 2021)
This study aims to determine the financial distress condition of food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018. The sampling technique used is purposive sampling. This research was conducted on 9 food and beverage companies listed on the Indonesia Stock Exchange for the period 2014-2018. The type of data used in this study is secondary data obtained from the website www.idx.co.id. The method used to analyze financial distress is the Altman Z-Score Modification method using 4 variables X1 X2 X3 and X4. Has the formula Z” = 6.56X1 + 3.26X2 + 6.72X3 + 1.05X4. Z-Score rating category > 2.6 is in the Safe Zone, 1.1 < Z-Score > 2.6 is in the Ash Zone gray so that the possibility of being saved and the possibility of going bankrupt is equally dependent on the decision of the company's management as the decision maker. Z-Score <1.1 is in the Danger Zone categorized as a company experiencing financial difficulties and at high risk of bankruptcy. The results showed that 2 companies were in the Danger Zone, including: PT Tri Banyan Tirta Tbk and PT Prasidha Aneka Niaga Tbk, 4 companies were always in the Safe Zone, including: PT Wilmar Cahaya Indonesia tbk, PT Delta Djakarta Tbk, PT Nippon Indosari Corpindo Tbk and PT Siantar Top tbk, 3 other companies are in the Gray Zone, including: PT Multi Bintang Indonesia Tbk, PT Sekar Bumi Tbk and PT Sekar Laut Tbk